2010
DOI: 10.1063/1.3458797
|View full text |Cite
|
Sign up to set email alerts
|

A simple alcohol-chemical vapor deposition synthesis of single-layer graphenes using flash cooling

Abstract: We report the synthesis of single-layer graphenes from ethanol using, what we call, “flash cooling” just after chemical vapor deposition. The single-layer graphenes synthesized are high-quality and several micrometers in grain size as revealed by Raman spectroscopy. Detailed comparison of the cooling processes suggests that the single-layer graphene growth does not occur during the carbon precipitation but rather stems from surface diffusions of carbon on a nickel substrate. Because of the present simple and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 18 publications
1
64
0
Order By: Relevance
“…Graphene layer growth on Ni substrate with this precursor has been demonstrated [12,13]. Here graphene films were grown on copper foil using a mixture of argon and ethanol, for comparing with the methane grown films.…”
Section: Resultsmentioning
confidence: 99%
“…Graphene layer growth on Ni substrate with this precursor has been demonstrated [12,13]. Here graphene films were grown on copper foil using a mixture of argon and ethanol, for comparing with the methane grown films.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the CVD growth of graphene occurs through two different growth processes such as the carbon dissolution into metals and the surface diffusion of carbon on metal surface. 20,21 The result shown in Fig. 2 indicates that ex-situ annealing promotes dissolution, resulting in the formation of graphene.…”
Section: And T Egawamentioning
confidence: 85%
“…Cracks might be created in the last stage of CVD process, that is during rapid cooling stage. This stage, as a last part of the CVD process, is necessary to obtain high quality graphene [23].…”
Section: Graphene Surface Morphologymentioning
confidence: 99%
“…The authors demonstrated elevated I 2D /I G ratios in comparison with Cu. Common features of the above cited works are: Cu substrate (with the exception of [23]), hydrogen assistance and the fact that graphene sheets had been transferred onto other substrates (usually SiO 2 /Si) prior to the actual characterization. In this work we present a comparative analysis of large-area graphene sheets grown on a polycrystalline Cu foil from two different types of carbon precursors, namely liquid (ethanol) versus conventional gaseous (methane).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation